English as a Foreign Language Learners’ Well-Being and Their Academic Engagement: The Mediating Role of English as a Foreign Language Learners’ Self-Efficacy - Jia, Hui (Frontiers in Psychology, 2022)
Well-being is a crucial necessity within the educational setting that is also taken into account as a central aspect of people’s inclination in the subject of Positive Psychology (PP) study which is vital for learners’ affective equilibrium and proper development and improvement. Likewise, learners’ engagement has been demonstrated to have a fundamental function in education. A great amount of attention has been given to this concept and its possible indicators because of its role at the core of learners’ educational achievement. Alternatively, it is commonly maintained that self-efficacy has turned into a significant mental concept enhancing the educational cycle and educational presentation that influences learners’ decisions regarding their educational assignment and manners and their way of thinking and feeling when it comes to education. This review attempts to survey the role of learners’ self-efficacy as a mediator on their well-being and academic engagement. In conclusion, some suggestions and commendations have been proposed for language teaching participants in scholastic situations.